PROSES PERKEMBANGAN DESA WISATA KECAMATAN PADANG PANJANG TIMUR KOTA PADANG PANJANG (Studi Kasus : Desa Kubu Gadang dan Kampung Sigando) - Mustika, Diva Tri (JURNAL BUANA, 2026)
Padang Panjang Timur District, Padang Panjang City, has tourist village destinations, namely the Kubu Gadang Tourism Village and the Sigando Cultural and Religious Village Tourism Village. The aim of this research is to find out: 1) the landscape conditions of Nagari Kubu Gadang and Sigando Religious Cultural Village, 2) community involvement in the development of Kubu Gadang Village and Sigando Religious Cultural Village, 3) the development process of Kubu Gadang Village and Sigando Religious Cultural Village as a tourist village. The method used is the mixed methods or a mixture of Quantitative and Qualitative. The research results are: 1) After processing the data using Arcgis, the landscape conditions of the two villages were obtained, the beauty of which can be observed from certain sides. 2) Processing the interview data using the POET method shows that the two tourist destinations all involve the community in their development process. 3) Data processing using the TALC method and it was found that the development phase of the Kubu Gadang Tourism Village was at the consolidation stage or was already starting to progress and secondly the Sigando Cultural and Religious Village was at the involvement stage or still in the development process.